Leave your trace – the virtual time machine. Issue 2 (1st December 2014) - Oh, Selavy; Glasauer, Stefan
Our dependence on digital data, be it for knowledge, images or for records of personal history, is growing increasingly due to almost indefinite storage space and global availability. However, this dependence shifts our being and our life successively into the virtual: the memories of childhood are no longer fading pictures in an old photographic album, but jpegs on an old data disk. Here we show, using a virtual world, that digitization and virtualization of our world has its drawbacks. We propose a time machine that allows visiting the past and, under certain circumstances, even changing the present. This time machine can be realized in a virtual world: digital data can be recorded and stored continuously for revisiting at will. Our virtual time machine has unsettling implications, which have parallels in contemporary surveillance and data collection programmes: not only would the complete past be open for investigation, the time machine would, under certain restrictions such as avoiding inconsistencies in the time stream, allow changing the past as normative intervention in history. Modifying the past would even permit influencing the present. To prevent or at least complicate modifications of our personal history by malevolent access to our digital data, we recommend leaving traces in the world.